PROSPECTS OF DEVELOPMENT OF HOUSING CONSTRUCTION - E. Bogomolova; A. Kozlovskiy; N. Moiseenko (Вестник университета)
Actual problems of development of housing construction in modern economic conditions are considered in the article. Questions of land tenure and allocation of sites under housing construction, strategy of expenses in this segment, state sale and others has been consistently analyzed. The principles and approaches to the analysis of the housing construction has been defined. The comparative dynamics of functioning of the market of construction real estate has been presented. The attention is paid to possibilities of the private-state partnership and co-investing habitation civil-engineering designs. The issues of distribution of shares between participants in housing construction are considered. Offers under the decision of tasks in view are given.